Juvenile competitive triathlete after cardiotoxic anthracycline therapy for Acute Myeloid Leukemia. Issue 1 (December 2016) - von Korn, Pia; Vogt, Manfred; Oberhoffer, Renate; Ewert, Peter; Müller, Jan
Abstract Objective The treatment of Acute Myeloid Leukemia (AML) leads to several functional limitations. Especially cardiac burden following cardiotoxic chemotherapy, which limits exercise and competitive sport in the long-term survivors. Subject and methods We report on a young female amateur triathlete born in 1997, who was diagnosed with AML at the age of fifteen. She had chemotherapy with a cumulative dose of about 1000 mg/m2 anthracyclines and allogeneic stem cell transplantation which was successful, but she suffered from cardiotoxic systolic heart failure with a left ventricular ejection fraction (LVEF) <55 % and an impaired peak oxygen uptake of 23.2 ml/min/kg and 53 % of predicted, respectively. After medical examination and counselling with a sport scientist she started a tailored training of aerobic exercise. She was evaluated at regular intervals which resulted in increasing the training load and volume. Eventually her training hours was stepwise increased to 12 h training per week, which includes high intensity intervals. Results Within almost 3 years, her exercise performance improved tremendously. Workload doubled from 2.1 W/kg to 4.2 W/kg, peak oxygen uptake increased from 23.2 ml/min/kg to 49.1 ml/min/kg and from 53 to 135 %, respectively. Moreover, she participated in several competitions. However, LVEF remains almost unchanged. Conclusion With the right training and under medical surveillance competitive exercise with an anthracycline-damaged heart is still achievable. Moreover, competitive training and exercise seems to be safe and feasible.